2016
DOI: 10.22159/ajpcr.2017.v10i1.14500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Treatment-Seeking Behavior and the Related Factors Among the Dwellers of Safashahr City

Abstract: Objective: The present study aims to recognize and evaluate treatment-seeking behavior and the related factors among the dwellers of Safashahr city. Methods:The current applied research is cross-sectional with a population size of 380 and executed in a systematic random sampling among the dwellers of Safashahr city and the villages governed by it. SPSS version 22 has been utilized for analyzing the data in this study. T-test, Chi-square variance analysis, Pearson test, and Spearman test have been used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…This positive association was similarly described in a study in Senegal that found an increase in the odds of seeking healthcare among people older than 40 years, (28) contradicting the ndings of another study conducted in Iran that revealed an inverse relationship between age and appropriate HSB, where older people were less likely to seek healthcare. (10) Monthly Income…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…This positive association was similarly described in a study in Senegal that found an increase in the odds of seeking healthcare among people older than 40 years, (28) contradicting the ndings of another study conducted in Iran that revealed an inverse relationship between age and appropriate HSB, where older people were less likely to seek healthcare. (10) Monthly Income…”
Section: Agementioning
confidence: 99%
“…Studies suggest that there is a positive relationship between the availability and quality of health services and their utilization, i.e., healthseeking behavior(6-9) nevertheless, some inequalities in access to these services have been observed, indicating that patients from lower social and economic positions, as well as certain nationalities and minority groups, bene t less from these advantages. (10) According to recent International Organization of Migration (IOM) estimations, there were approximately 281 million international migrants worldwide in 2020 (11) whose lives were in uenced by social factors in their home countries and who were confronted with new social, economic, and political conditions in the nations where they migrated. In particular, labor migration has been linked to high stress levels, poor working conditions, and poor psychological and physical health.…”
Section: Introductionmentioning
confidence: 99%